2015
DOI: 10.1073/pnas.1512913112
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic P-Rex1 signaling regulates hippocampal long-term depression and autism-like social behavior

Abstract: Autism spectrum disorders (ASDs) are a group of highly inheritable mental disorders associated with synaptic dysfunction, but the underlying cellular and molecular mechanisms remain to be clarified. Here we report that autism in Chinese Han population is associated with genetic variations and copy number deletion of P-Rex1 (phosphatidylinositol-3,4,5-trisphosphate-dependent Rac exchange factor 1). Genetic deletion or knockdown of P-Rex1 in the CA1 region of the hippocampus in mice resulted in autism-like socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 48 publications
0
78
0
Order By: Relevance
“…The cytoplasmic FMRP-interacting protein (CYFIP) directly links Rac1 and FMRP to modulate cytoskeleton remodeling (45); Tsc1 functionally regulates Rac1 activity (46,60); Ube3a promotes Rho-GEF Pbl degradation via ubiquitination to affect Rac1 activation (47); and upon synaptic activation Rho-GEF Kal-7 disassembles from the Nrx-1/Nlg4/DISC1 complex to modulate the Rac1 pathway (48). Several other autism-risk genes, such as Nlg1, Nrx-4, P-Rex1, and Shank-3, have also been reported to participate in the Rac1-signaling pathway (61)(62)(63)(64). In addition, when the gene-environment interactions of 122 genes and 191 factors in the autistic context were analyzed by systems biology, Rac1 was predicted to be a converging node that genetically links to the neurobiology of autism (27,65)…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasmic FMRP-interacting protein (CYFIP) directly links Rac1 and FMRP to modulate cytoskeleton remodeling (45); Tsc1 functionally regulates Rac1 activity (46,60); Ube3a promotes Rho-GEF Pbl degradation via ubiquitination to affect Rac1 activation (47); and upon synaptic activation Rho-GEF Kal-7 disassembles from the Nrx-1/Nlg4/DISC1 complex to modulate the Rac1 pathway (48). Several other autism-risk genes, such as Nlg1, Nrx-4, P-Rex1, and Shank-3, have also been reported to participate in the Rac1-signaling pathway (61)(62)(63)(64). In addition, when the gene-environment interactions of 122 genes and 191 factors in the autistic context were analyzed by systems biology, Rac1 was predicted to be a converging node that genetically links to the neurobiology of autism (27,65)…”
Section: Discussionmentioning
confidence: 99%
“…One systems biology study based on gene-expression analysis of cerebellar samples concluded that Rac1 plays a critical role in the neuropathological events associated with ASD (Zeidán-Chuliá F, et al, 2013). Another recent study found that autism is associated with genetic variation and copy number deletion of P-Rex1, which encodes phosphatidylinositol-3,4,5-trisphosphate-dependent Rac exchange factor 1 (Li et al, 2015). Genetic deletion or knockdown of P-Rex1 in the CA1 region of the mouse hippocampus produces ASD-like behaviors, including impaired social interactions, reversal learning deficits in the water maze, and extinction-resistant memory of fear conditioning.…”
Section: Active Forgetting Autism Spectrum Disorders and Other Brainmentioning
confidence: 99%
“…Prex1 results in autismlike behavior 36 and is associated with antidepressant response in humans 37 . Interestingly, very few associations that were detected in deconvoluted neurons (1 CpG) or glia (14 CpGs) were also detected in bulk, suggesting celltypespecific effects are indeed diluted or obscured in bulk tissue.…”
Section: Bulk Brainmentioning
confidence: 99%